2012
DOI: 10.1248/bpb.35.369
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide Ameliorates Insulin Resistance and Fatty Liver in Obese Mice

Abstract: Fenretinide (FEN), a ligand of retinol binding protein 4 (RBP4), has been suggested as a measure to reduce insulin resistance and its associated disorders such as obesity, and fatty liver by reducing serum RBP4. We investigated whether there is another possible mechanism by which fenretinide reduces insulin resistance and fatty liver in genetically obese (ob/ob) mice. Male obese mice fed a high-fat diet (45% of calories from fat) were divided into two groups (n 13 each). One (FEN) received fenretinide (20 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…Many adipokines are implicated directly in the pathologies associated with obesity, particularly the metabolic syndromes [18]. RBP4 is a compact and globular protein that was first identified as a retinol carrier, and is mainly synthesized and secreted by the liver [19]. Recently, an increasing body of evidence has identified RBP4 as an adipokine and elevated RBP4 expression is closely related to insulin resistance and type 2 diabetes [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many adipokines are implicated directly in the pathologies associated with obesity, particularly the metabolic syndromes [18]. RBP4 is a compact and globular protein that was first identified as a retinol carrier, and is mainly synthesized and secreted by the liver [19]. Recently, an increasing body of evidence has identified RBP4 as an adipokine and elevated RBP4 expression is closely related to insulin resistance and type 2 diabetes [20].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence from both clinical and experimental studies have corroborated that elevated serum RBP4 level contributes to systemic insulin resistance and is associated with metabolic disorders, including diabetes, dyslipidemia, and cardiovascular risk factors [4,5,6]. Suppression of serum RBP4 by fenretinide, which increases urinary excretion of RBP4, improves insulin resistance and glucose intolerance [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Fenretinide is a synthetic retinoid and anticancer agent that reduces serum RBP-4 levels by interfering with RBP-4 binding to transthyretin resulting in an improvement in insulin sensitivity [16,17]. In an experimental study, fenretinide, a ligand of RBP-4, was given to genetically obese (ob/ob) mice [18]. Plasma RBP-4 levels were decreased and adiponectin levels were increased significantly with fenretinide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with animal studies that have shown that reduction in plasma rbp4 level using RNA oligonucleotide against rbp4 in high-fat diet-fed mice or using a ligand of rbp4 in ob/ob mice induces a significant reduction in plasma triglycerides. 16,37 To precisely determine the association between plasma rbp4 and triglycerides and to explore a possible link between elevated plasma rbp4 levels and hypertriglyceridemia, in T2DM, we performed an in vivo kinetic study of apoB-containing lipoproteins (VLDL, IDL, LDL) with stable isotopes in a group of 14 patients with T2DM. The results of our kinetic study clearly show that rbp4 is negatively associated with the catabolism of VLDL-apoB100 and that this relationship is independent of triglycerides, age, sex, BMI, HbA1c, HDL-C, and markers of insulin resistance, such as homeostasis model assessment of insulin resistance or plasma adiponectin level.…”
Section: Discussionmentioning
confidence: 99%